1982
DOI: 10.1007/bf01965144
|View full text |Cite
|
Sign up to set email alerts
|

Tissue histamine levels in male and female normal and nude mice

Abstract: In comparison with those in normal (+/+) mice, tissue histamine levels were lower in athymic (nu/nu) female mice and higher in athymic male mice. The sexual difference was less marked or absent in nu/nu mice. These results show (a) that endocrine factors are involved in the distribution of tissue histamine, and (b) that the thymus cannot be considered as the main source of tissue histamine in pathogen-free mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
3
2

Year Published

1985
1985
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 11 publications
3
3
2
Order By: Relevance
“…Histological study of the ovaries and testes of normal and genetically sterile animals collected 0 to 28 days postnatal has demonstrated that the few ova and spermatogonia found in gonads of W/W v mice develop more slowly than do the much larger numbers in the gonads of normal littermates [17]. The absence of sexual difference in tissue histamine levels of W/W v mice is in accordance with results obtained in nude mice which present endocrine disturbances [18]. Moreover, in normal mice, after ovariectomy, tissue histamine levels decreased while they increased after castration of males [19].…”
Section: Discussionsupporting
confidence: 87%
“…Histological study of the ovaries and testes of normal and genetically sterile animals collected 0 to 28 days postnatal has demonstrated that the few ova and spermatogonia found in gonads of W/W v mice develop more slowly than do the much larger numbers in the gonads of normal littermates [17]. The absence of sexual difference in tissue histamine levels of W/W v mice is in accordance with results obtained in nude mice which present endocrine disturbances [18]. Moreover, in normal mice, after ovariectomy, tissue histamine levels decreased while they increased after castration of males [19].…”
Section: Discussionsupporting
confidence: 87%
“…Very high concentrations of histamine in the stomach had been detected already previously [14,15]. However, in these latter studies, the values found were about twice as high as those found in the present study.…”
Section: Stomachcontrasting
confidence: 55%
“…In the skin of this mouse, the histamine concentration and the number of mast cells were also reported to be increased (histamine: 1.7-fold; number of cells: 3-4-fold) (3,8,19), but the increases were not as great as that in SHT observed in this study. In an athymic rat (rnu/rnu), the number of mast cells in the subepidermis but not in the deep dermis was reported to be increased compared with the control rat (1).…”
Section: Discussioncontrasting
confidence: 44%
“…The inability of the thymus-deficient nude mouse to accumulate mucosal mast cells in response to a nematode infection also suggested the dependency of mucosal mast cells on the thymus (14). In other studies, however, the differentiation was demonstrated to be independent of the thymus or T cells (3,9,11). It was also reported that the thymus suppresses the dif- €¢Z"I|l_q:,< §,?t" ' "' €- §:-555!…”
Section: Discussionmentioning
confidence: 86%